“Varlık Dağını Delmek”: İbnü’l-Arabî’nin Eserleri Esâsında Varlık, Tecrübe ve Ahlâk Açısından Aşk - GEMUHLUOĞLU, ZEYNEP (My University, 2020)
Bu çalışma, İbnü’l-Arabî’nin eserlerindeki aşk konusunu varlık, tecrübe ve ahlakmerkezinde incelemeyi hedeflemektedir. İnceleme, aynı zamanda söz konusu alanlarda İbnü’l-Arabî ve Grek ve İslam felsefi okulları arasındaki farklara işaret etmeyi hedeflemektedir. Giriş bölümünde Grek felsefesinin aşk konusundaki zemini incelenirken, birinci bölümde İbnü’l-Arabî’nin eserlerinde varlık-oluş ilişkisinin aşk ile ilgisi ele alınmaktadır. İkinci bölümde Kalp, Ruh, Nefs, Hevâ, Akıl ilişkisi, üçüncü bölümde ise aşk ve tecrübe ilişkisinin ahlaki sonuçları değerlendirilmektedir

This study aims to examine the subject of love in the main books of Ibn al-Arabî with respect to existence, experience and ethics. The study also aims to point out the differences between Ibn al-Arabi and Greek and Islamic philosophical schools regarding these topics. In the introduction, the foundations of the Greek philosophy on the subject of love are explored. In the first chapter, the relationship between being and love in Ibn Arabi’s main works are examined. Later on, in the second part, the relationship between Heart, Spirit, Soul (Nafs), Hawa, and Reason, and finally, in the third part, the ethical consequences of the relationship between love and experience are studied.
“To Pierce Through the Mountain of Being”: Love in Terms of Being, Experience and Ethics According to Ibn Arabi’s Books